WHEN FACT-CHECKING IS NOT WEIRD: CHALLENGES IN FACT-CHECKING BEYOND THE WESTERN WORLD - Vinhas, Otávio Iost; Bastos, Marco (AoIR Selected Papers of Internet Research, 2023)
Fact-checking has rapidly achieved a pivotal role in regulating the public debate globally. Reports show that the fact-checking industry is becoming more diverse, operating across more cultures and languages of recent. However, literature on fact-checking beyond the West is still forthcoming, as empirical research is disproportionally focused on the US. In this paper, we seek to catalog the many different forms of organizing and implementing fact-checks beyond the de facto standard found in Western industrialized countries, where fact-checking streams from journalistic verification practices. We analyzed 37 semi-structured, in-depth interviews with fact-checkers from 35 organizations operating in 27 non-WEIRD (Western, Educated, Industrialized, Rich, and Democratic) countries in Africa, Asia, Latin America, and Eastern Europe. The interviews were conducted in three different languages (English, Portuguese, and Spanish) between March and November of 2021. Interview data was transcribed and translated for downstream analyses using thematic clustering in N-Vivo. Findings show that non-WEIRD fact-checkers endure similar challenges to those reported in Western fact-checking organizations. These challenges are identified through an analysis of seven types of challenges common to non-WEIRD fact-checking organizations, which are associated with and speak to institutional, infrastructural, political, methodological, social, cultural, and linguistic dimensions. We concluded that while fact-checkers are relentless in promoting democratic values worldwide, the standards that support the industry may vary substantially around the world, particularly where truth-seeking practices evolved detached from notions of democracy, truth, and journalistic integrity.